The role of the B lymphocytes in endometriosis: A systematic review. (September 2017) - Riccio, L.G.C.; Baracat, E.C.; Chapron, C.; Batteux, F.; Abrão, M.S.
Highlights: The role of the immune system in endometriosis is not completely understood. Increased B lymphocytes and production of autoantibodies have been described. Flow cytometry could be a valuable tool to evaluate different B cells phenotypes. It is necessary to clarify the role of B cells and perhaps propose new treatments. Abstract: The physiopathology of endometriosis is not completely understood and its progression is associated with a local and systemic inflammatory reaction. It is important to clarify the potential role of the immune system to better understand its implication in the pathogenesis of endometriosis, which includes the study of the role of B cells and antibodies. The aim of this study was to review the literature about the role of B lymphocytes in endometriosis. A search for " endometriosis ", " B cell s" and " B lymphocytes " in databases resulted in 140 citations; after applying inclusion and exclusion criteria, a total of 22 studies were assessed. The analyzed samples in the studies varied and different markers and techniques were used by the authors to evaluate the direct or indirect role of B lymphocytes in endometriosis. Most studies demonstrated increased number and/or activation of B cells while seven studies found no difference and two studies showed decreased number of B cells. Increased B lymphocytes and excessive production of autoantibodies in endometriosis have been described in the literature, but their role in the development of the disease is not well understood. Moreover, the association of these factors with clinical symptoms, location and severity of the disease has not been investigated. Further studies are necessary to clarify the role of B cells in the development of endometriosis and propose new therapeutic strategies such as the use of drugs that target these cells.